What determines the size of occupational health services in UK universities? - Venables, K; Allender, S (2007)
BACKGROUND: There is wide, largely unexplained, variation in occupational health (OH) provision between UK employers. AIM: To explain the variation in OH provision across the UK university sector. METHODS: Analyses of data from a survey of university OH services and from the Higher Education Statistics Agency. The outcome variable was clinical (doctor + nurse) staffing of the university's OH service. The explanatory variables examined were university size, income, research activity score and presence or absence of academic disciplines categorized by an expert panel as requiring a high level of OH provision. RESULTS: All 117 UK universities were included and 93 (79%) responded; with exclusions and incomplete data, between 80 and 89 were included in analyses. There was wide variation in clinical OH staffing (range 0-8.4 full-time equivalents). Number of university staff explained 34% of the variation in OH staffing. After adjusting for other factors, neither the research activity nor the presence of high-needs disciplines appeared to be factors currently used by employers to determine their investment in OH. CONCLUSIONS: Government or other guidelines for university employers should take organizational size into account. Employers may need guidance on how to provide OH services proportionate to specific occupational hazards or other OH needs.